Identification of bacterial morphology and catalase coagulation test on propionibacterium acnes bacteria - M. Andi Chandra (Surya Hijau Manfaat, 2023)
Infection is a way for microorganisms such as bacteria, viruses and fungi to enter the skin which can cause skin problems such as acne. purpose of this study was to determine the morphology of p. acnes by gram staining method, then the catalase test was used to determine the ability of microorganisms to decompose hydrogen peroxide by producing catalase enzymes and coagulase test is a bacterial examination to detect the formation of coagulase enzymes that bind to the bacterial cell wall. The results obtained were that the morphology of the bacteria was in the form of salt and purple in color, the catalase test was positive and the coagulase test was positive. The conclusion obtained was that P. acnes ATCC 11827 was included in the group of gram-positive bacteria based on the results of gram staining and catalase and coagulase tests.